Dynamics of Creativity In the Development of Intellectual Capacity of Youth (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article reveals the creative aspects of increasing the intellectual potential of young people. Also, on the one hand, the innovative activity of young people is seen as a person who is distinguished by activity, quick reactions, is interested in everyone and is not afraid of new situations, and on the other hand, the dynamic factors of the manifestation of characteristics such as being careful, tending to follow learned rules, and being afraid of something new have been studied.